Reproductive change in India and Brazil - Martine, George ed.; Martine, George ed.; Das Gupta, Monica ed.; Chen, Lincoln C. (Delhi : Oxford University Press, 1998)
Papers presented at various seminars held during 1995-1996.
Includes bibliographical references and indexes.
Keywords: Birth control -- India; Birth control -- Brazil; Fertility, Human -- India; Fertility, Human -- Brazil